The Policy, Fiscal and Legal aspects relating to Oil Exploration in South Africa - Boswarva, Ernest (Department of Commercial Law, 2021)
This thesis is a textual analysis of the fiscal and legal aspects relating to the exploration and exploitation for oil and gas. The need for promotion of the exploration and exploitation of oil and gas and the fiscal and legal aspects relating thereto. The different types of legal agreements commonly found in transactions between the State and the private international investor are cited as are the implications of the different types of taxes levied by the State in order to collect its 'take' in the national resource. The method of taxation of oil in South Africa is examined with special reference to the prospecting lease OP26 granted by the State to SOEKOR (Pty) Limited.